Immobilization of metallporphyrins on polystyrene: efficient catalysts for aerobic oxidation of alcohols - Naik, R.; Joshi, P.; Deshpande, R. K. (Journal of Molecular Catalysis A-Chemical, 2005)
Metalloporphyrins of iron and cobalt have been successfully encapsulated for the first time using polystyrene matrix, exhibiting high activity for aerobic oxidation of alcohols mimicking cytochrome P-450 dependent mono oxygenases. This communication provides a simple and environmentally friendly protocol for immobilization of metalloporphyrins (MPs) on to polystyrenes in general, which gives stable,I reusable (see Footnote 1) and efficient catalysts for aerobic oxidation of alcohols. These catalysts were characterized by UV-vis as well as diffuse reflectance FT-IR spectroscopy. These catalysts not only have high turnover frequencies but also could be recovered quantitatively by simple filtration and reused without loss of activity. Considering their high dispersing capacity in organic solvents, they will definitely find broad spectrum of applications in the electronic as well as optical fields. This methodology will lead to a potential model to mimic the catalytic action of metalloporphyrins in the niche areas such as catalytic oxidations, drug metabolism, DNA cleavage, photodynamic therapy and many others. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Immobilization; metalloporphyrins; micro-encapsulation; Polystyrene; turnover frequency

Synthesis, characterization and catalytic activity of Mn(III)- and Co(II)-salen complexes immobilized mesoporous alumina - Chaube, V. D.; Shylesh, S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Mn(III) and Co(II)-schiff base complexes were immobilized over mesoporous alumina through the reaction of mesoporous alumina functionalized 3-aminopropyl triethoxy silane (3-APTES) and salicylic aldehyde via schiff base condensation. The surface properties of the functionalized catalysts were analyzed by a series of characterization techniques like elemental analysis, PXRD, FTIR, N(2) adsorption-desorption, TG-DTG, DR UV-vis, XPS, etc. PXRD and adsorption-desorption analysis shows that the mesostructure of alumina remains intact after various modifications, while spectral technique show the successful anchoring of the neat complexes inside the porous alumina support. The catalytic activity of the functionalized metal-salen complexes examined in the liquid phase oxidation of styrene and cyclohexene shows that the functionalized salen complexes are more active and selective than the corresponding neat metal complexes. Further, the catalyst (Mn-S-NH(2)-MA) was recycled three times in the oxidation of styrene and no major change in the conversion and selectivity is observed, which shows that the immobilized metal-salen complexes are stable under the present reaction conditions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Immobilization; Mesoporous alumina; Oxidation; Schiff base complexes

Ossification: a new approach to immobilize metal complex catalysts - applications to carbonylation and Suzuki coupling reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Journal of Catalysis, 2006)
A simple approach for immobilization of transition metal complexes is reported here based on the transformation of the complex into its intrinsically insoluble counterpart, thus generating solid molecular catalysts. This approach that we call ``ossification'' is based on a principle, in which the water-soluble analogues of the metal complexes are precipitated out from aqueous solutions as insoluble ionic ensembles having catalytically active metal-centered coordination environments and robust framework. The approach has been illustrated for I'd complex catalyzed carbonylation and Suzuki coupling reactions. ``Ossification'' was found to be an economically and environmentally attractive alternative to other exotic immobilization methodologies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Carbonylation; Heterogeneous catalysts; Immobilization; ossification; Palladium complex; Suzuki coupling

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Immobilization of penicillin G acylase on amino functionalized mesoporous silica - Sridevi, N.; Pallavi, Shah; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
Penicillin G acylase was immobilized on Amino functionalized mesoporous silica by adsorption method. In this paper we present the effect of penicillin G acylase immobilization on amino-functionalized mesoporous silica and the effect of silica as host matrix on enzyme kinetics. The loading capacity of immobilized Penicillin G acylase is 34 mg protein per 0.5 g of SBA-15. About 65% of the protein was adsorbed on mesoporous silica. The stability of penicillin acylase was enhanced after immobilization on mesoporous silica. The adsorbed enzyme is more stable than the soluble form, both to temperature and pH environments and retained 73% of its activity.
Keywords: Amino functionalized mesoporous silica; Immobilization; Penicillin G acylase; pH and temperature stabilities

Lipase enzyme immobilization on synthetic beaded macroporous copolymers for kinetic resolution of chiral drugs intermediates - Bhushan, Indu; Parshad, Rajinder; Qazi, Gulam Nabi; Ingavle, Ganesh C.; Rajan, C. R.; Ponrathnam, Surendera; Gupta, Vijay Kumar (Process Biochemistry, 2008)
Lipase isolated from Arthrobacter sp. (bacterial strain, MTCC No. 5125) at RRL Jammu, being used for various process development. Arthrobacter sp. lipase (ABL) now has been immobilized on synthetic polymers and reused many a times. In this investigation number of various synthetic macroporous alkylated glycidyl epoxy copolymers with varying hydrophobicity, pore volume and surface area were prepared and used for this study. Among all the polymers prepared and used only two epoxy polymers GMA-EGDM 75-20(I) and GMA-EGDM 75-30(I) with particle size in the range of 150-450 nm, epoxy groups 80 and 70%, tertiary amino groups 20 and 30% was found suitable for immobilization of lipase (ABL). Dibutyl amine (DBA) incorporation created an internal pore radii 20-50 nm and hydrophobic microenvironment in both the polymers for binding the enzyme, which led to improvement in stability and enatioselectivity in racemic resolution process especially by binding to one of the isomers. The optimal ABL binding capacity of polymer GMA-EGDM 75-20(I) was 60 units, 34 mg protein and GMA-EGDM 75-30(l) was 36 units, 21 mg protein/g polymer. The immobilized lipase matrices displayed enhanced pH, thermal, organic solvent and long-term storage stability. Both the immobilized enzyme matrices were tested firstly for the hydrolysis of triglycerides using tributyrin as substrate. After testing, both the matrices were reused for racemic resolution of ethyl-3-hydroxy-3-phenyl propanoate (fluoxetine intermediate, an antidepressant drug) and racemic chiral auxiliary, acetyl-1-phenyl ethanol (intermediate of many chiral drugs) for 15 cycles. These immobilized lipase matrices have shown very high stability on recycling, high-enantioselectivity, high conversion and faster recovery of product compare to free enzyme, therefore these matrices may find use in kinetic resolution process developments. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-phenyl ethanol and enantioselectivity; chiral resolution; enantiomeric excess (ee); ethyl-3-hydroxy-3-phenyl propanoate; Immobilization; Lipase

Arthrobacter sp lipase immobilization for preparation of enantiopure masked beta-amino alcohols - Chaubey, Asha; Parshad, Rajinder; Gupta, Pankaj; Taneja, Subhash C.; Qazi, Ghulam N.; Rajan, C. R.; Ponrathnam, S. (Bioorganic & Medicinal Chemistry, 2009)
Recent reports on immobilization of lipase from Arthrobacter sp. (ABL, MTCC 5125; IIIM isolate) on insoluble polymers have shown altered properties including stability and enantioselectivity. Present work demonstrates a facile method for the preparation of enantiopure beta-amino alcohols by modulation of ABL enzyme properties via immobilization on insoluble as well as soluble supports using entrapment/covalent binding techniques. Efficacies of immobilized ABL on insoluble supports prepared from tetraethylorthosilicate/aminopropyltriethoxy silane and soluble supports derived from copolymerization of N-vinyl pyrrolidone-allylglycidyl ether (ANP type)/N-vinyl pyrrolidone-glycidyl methacrylate ( GNP type) for kinetic resolution of masked beta-amino alcohols have been studied vis-a-vis free ABL enzyme/wet cell biomass. The immobilized lipase on different insoluble/soluble supports has shown 21 - 110 mg/g protein binding and 30 - 700 U/g activity for hydrolyzing tributyrin substrate. The findings have shown a significant enhancement in enantioselectivity (ee 99%) vis-a-vis wet cell biomass providing ee 70-90% for resolution of beta-amino alcohols. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Arthrobacter sp lipase; beta-Aminoalcohol; Enantioselectivity; Immobilization; soluble polymer

Catalytic activity of cobalt containing MCM-41 and HMS in liquid phase oxidation of diphenylmethane - Bhoware, Shrikant S.; Kamble, K. R.; Singh, A. P. (Catalysis Letters, 2009)
Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80 A degrees C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was examined with different polar and non polar solvents. Oxidation of diphenylmethane in solvent free media (under similar reaction conditions) shows formation of hydroxy derivatives of benzophenone in addition to main product (benzophenone). Hundred percent selectivity to benzophenone was obtained when the reaction was carried out in solvent.
Keywords: diphenylmethane; HMS; Immobilization; MCM-41; XRD

Immobilized invertase - Kotwal, S. M.; Shankar, V. (Biotechnology Advances, 2009)
Invertase is a commercially important enzyme used for the hydrolysis of sucrose. The hydrolysis of sucrose yields an equimolar mixture of glucose and fructose, known as invert syrup, is widely used in food and beverage industries. This enzyme is also used for the manufacture of artificial honey, plasticizing agents used in cosmetics, pharmaceutical and paper industries as well as enzyme electrodes for the detection of sucrose. Immobilization of invertase and its biotechnological applications are reviewed. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Applications; Immobilization; Invert syrup; Saccharase

Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

Continuous phenol biodegradation in a simple packed bed bioreactor of calcium alginate-immobilized Candida tropicalis (NCIM 3556) - Varma, R. J.; Gaikwad, B. G. (World Journal of Microbiology & Biotechnology, 2010)
Phenol biodegradation in a continuous system of immobilized Candida tropicalis NCIM 3556 was studied. The bioreactor was simple, it had a feed inlet from the bottom and the effluent outlet from top, no supplementary oxygen was supplied, the reactor was operated continuously for 116 days. Initially the column was run continuously with a feed concentration of 2 g l(-1) for 42 days whence a degradation of > 97% was achieved. The feed concentration was then increased to 3 g l(-1), for which a similar to 80% biodegradation was sustained for 90 days after which there was a steady decrease in the performance. When the phenol degradation was reduced to similar to 50% in 116 days, the reactor was stopped. The efficiency of free cells recycled every 24 h and immobilized cells were compared; it was estimated that repeated reuse of free cells in batch mode gave an overall efficiency of 0.102 g phenol degradation g(-1) cell wet weight in 12 days. In contrast, the immobilized system of the same biomass had a longer working lifetime of similar to 4 months indicating an efficiency of 3.72 g phenol g(-1) cell wet wt.
Keywords: Biodegradation; Ca alginate; Candida tropicalis; Immobilization; phenol

Studies of penicillin G acylase immobilization using highly porous cellulose-based polymeric membrane - Adikane, H. V.; Thakar, D. M. (Applied Biochemistry and Biotechnology, 2010)
The different ionic molecules/compounds were used as a ligand for the immobilization of penicillin G acylase on the highly porous cellulose-based polymeric membrane having buffer flux 1,746 LMH (L m(-2) h(-1)) at 0.5 bar pressure. The immobilized enzyme activity around 250 U-App was obtained with the ligand such as proline, tryptophan, casein acid hydrolysate, and brilliant green. Comparatively, proline showed less IMY% (percentage immobilization yield-58) but higher RTA% (percentage of activity retention-71) and specific activity (145 U-App g(-1)). However, the crosslinked preparation of brilliant green obtained using glutaraldehyde showed 82 +/- 2.7% immobilized enzyme activity after the completion of successive five cycles. In comparison with the free enzyme, the enzyme immobilized on the brilliant green coupled membrane showed around 2.4-fold increase in K-m value (47.4 mM) as well as similar optimum pH (7.2) and temperature (40 degrees C). The immobilized enzyme retained almost 50% activity after 107 days and 50 cycles of operation. Almost 50% decrease in buffer flux after enzyme immobilization was observed. At the end of the 30 cycles, flux pattern shows around 38% decrease in buffer flux however, after 16 cycles of operation flux moves closer towards the steady state.
Keywords: Brilliant green; Immobilization; Penicillin G acylase; Polymeric membrane; Proline

Immobilization of conidiobolus coronatus alkaline protease on waste fungal biomass - Shankar, Shiv; Laxman, Ryali Seeta (Environmental Engineering and Management Journal, 2011)
Alkaline protease from Conidiobolus coronatus which is optimally active at pH 10 and 40 degrees C finds application in leather and detergent industries as well as for recovery of silver from waste photographic films. The protease was immobilized in Ca-alginate, polyacrylamide gel and alkali treated waste fungal biomass (ATWFB). ATWFB was found to be most suitable among the matrices tested. Glutaraldehyde marginally increased the binding to ATWFB. Binding of protease to ATWFB seems to be through adsorption as confirmed by FTIR spectra. Though temperature optima of free and immobilized proteases were identical, optimum pH of the immobilized enzyme shifted to 11 from 10. Temperature stability of the protease increased after immobilization. Immobilized protease could be reused 3 times with marginal loss in activity.
Keywords: Alkaline Protease; Conidiobolus coronatus; fungal biomass; Immobilization

Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose

Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution

Anchored Pd-complexes in mesoporous supports: synthesis, characterization and catalysis studies for carbonylation reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Catalysis Today, 2012)
Pd(pyca)(PPh3)(OTs) [pyca = 2-picolinate] complex is efficiently anchored inside different mesoporous matrices, such as MCM-41, MCM-48, SBA-15 using a molecular aminopropyl tether moiety employing different synthesis strategies. Thorough characterization of the materials using powder XRD, multinuclear (C-13, Si-29, P-31) CP-MAS NMR, XPS, SEM, N-2-sorption studies etc. confirmed the successful anchoring of the palladium complex to the walls of the support matrices thus establishing the synthesis protocols unambiguously. The catalysts were found to be highly active and selective for the carbonylation of different aryl olefins and alcohols. Consecutive recycling and successful reuse proved the stability and true heterogeneous nature of all the anchored catalysts, which is a substantial advancement over the existing heterogeneous catalysts for carbonylation. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Anchored catalysts; Carbonylation; Immobilization; mesoporous materials; Palladium complex

Gellan Gum a novel polysaccharide matrix for immobilization of thermo-tolerant yeast cells with invertase activity: factorial design and rheological studies - Sulabha, Karandikar; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The microbial extracellular polysaccharide gellan gum has been explored for its application in whole cell immobilization. Preliminary evaluation of the physicochemical properties of gellan gum in the presence of monovalent cation tetramethyl ammonium chloride (TMACl) was carried out. Gellan gum immobilized cells demonstrated better rheological properties than gellan gum. Attempts have been made to reveal the evaluation of gellan gum as a matrix to immobilize a thermotolerant yeast Kluyveromyces marxianus NCYC 2675. A 3(2) factorial design was used to study the simultaneous effect of two variables. The effect of the polymer concentration and TMACl concentration on various dependent variables like gelling temperature, mean particle size and enzyme activity of the yeast cells was studied. A statistical model with a significant interaction term was obtained to predict the results. Further, optimized immobilized system was evaluated with significant storage stability at 10 C and enhanced reusability with maximum conversion of > 90 % when crosslinked with glutaraldehyde.
Keywords: Gellan gum; Glutaraldehyde; Immobilization; invertase; Rheology; yeast cells

Gold nanoparticle embedded hydrogel matrices as catalysts: better dispersibility of nanoparticles in the gel matrix upon addition of N-bromosuccinimide leading to increased catalytic efficiency - Ramtenki, Vilas; Anumon, V. D.; Badiger, Manohar V.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2012)
A simple and convenient method for generating and immobilizing gold NPs into polyethylene glycol-polyurethane (PEGPU) matrices is presented. The gold NP immobilized PEGPU (Au NP-PEGPU) hydrogel matrices are easy to handle and can be used as catalysts. The efficiency, reusability and durability of the Au NP-PEGPU catalyst matrices were investigated using the reduction of 4-nitroaniline (4NA) to p-phenylenediamine (p-PDA) by sodium borohydride in the presence of the catalyst as a test reaction. The Au NPs in the PEGPU matrix got aggregated after 3 cycles of catalysis but dispersion could be regenerated by the addition of N-bromosuccinimide (NBS). After this regeneration process the Au NPs-PEGPU matrix showed excellent efficiency without any aggregation, leaching or degradation. The reusability of the catalyst for 28 cycles yielding a total turnover number of 3220 and turn over frequency of 0.152 s(-1) is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: catalysis; hydrogels; Immobilization; Nanoparticles; Turn over numbers

Immobilization of enantioselective lipase on soluble supports for kinetic resolution of drug intermediates - Chaubey, Asha; Parshad, Rajinder; Taneja, Subhash C.; Deokar, Sarika Babasaheb; Raman, Rajan C.; Ponrathnam, Surendra (Journal of Bioactive and Compatible Polymers, 2012)
The microbial lipase, Arthrobacter sp. lipase (MTCC 5125), from the Indian Institute of Integrative Medicine repository, is known as an effective catalyst for high enantioselective kinetic resolution of drug intermediates. The ABL was immobilized on water-soluble linear supports by covalently binding it to the epoxy groups on the N-vinyl pyrrolidone/allyl glycidyl ether and N-vinyl pyrrolidone/glycidyl methacrylate copolymers. The immobilized lipase, on different soluble supports, had 90-110 mg/g protein binding and 500-700 U/g hydrolysis activities for tributyrin substrate. These copolymers had soluble/insoluble characteristics in different pH ranges, which is an advantage over insoluble copolymers. A soluble polymer at neutral pH provided better accessibility to the immobilized enzyme, which was recovered by precipitation at pH 2-3 for reuse. Kinetic resolution of racemic acyl derivatives of chiral auxiliaries and drug intermediates, namely, phenyl ethanol, aminoalcohol, and fluoxetine intermediate resulted in a significant enhancement in enantioselectivity (99%).
Keywords: Arthrobacter sp lipase; Enantioselectivity; Immobilization; Kinetic resolution; N-vinylpyrrolidone; soluble polymer

Mn(III) based binapthyl schiff base complex hetrogenized over organo-modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Lazar, Anish; Singh, A. P. (Applied Catalysis A-General, 2012)
A heterogenized organocatalyst was synthesized by the covalent anchoring; of the complex chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di-tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) over modified mesoporous surface of SBA-15 through the reactive 3-aminopropyl trimethoxysilane (3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques such as elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, TGA-DTA, XPS, and solid state C-13 NMR. The XRD and N-2 sorption measurement, UV reflectance and CP MAS NMR spectroscopy (C-13 and Si-29) of the catalyst confirmed the structural integrity of the mesoporous hosts and the spectroscopic characterization technique proved the successful anchoring of the metal complex over the modified mesoporous support. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done in the oxidation reaction of thioanisole (methyl phenyl sulfide) by using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and turnover number (TON) and exhibit enhanced enantiomeric excess comparable to homogeneous catalyst [Mn(III)-L]. [Mn(III)-L-SBA-15] catalyst was found more active than homogeneous catalyst [Mn(III)-L]; Moreover bulkier alkene like 1,2-dihydronapthalene was also efficiently epoxidised with the synthesized supported catalyst. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Binaphthyl ligand; Chiral Schiff-base; Immobilization; Post grafting synthesis

Co-immobilized glucose oxidase and beta-galactosidase on bovine serum albumin coated allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer as a biosensor for lactose determination in milk - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Ponrathnam, Surendra (Enzyme and Microbial Technology, 2014)
Bovine serum albumin (BSA) was adsorbed on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) at pH 8.0 (16% w/w). The amino, thiol and carboxylic acid functional groups available on protein coated surface were utilized for covalent immobilization of glucose oxidase and beta-galactosidase, both independently, and in a step-wise manner on the same matrix, with no more than 10% loss of enzyme activity during immobilization. Glutaraldehyde cross-linking after immobilization provided stable enzyme preparations. The pH-optima of the immobilized enzymes were similar to those for free enzyme but their thermal stability was vastly improved. The co-immobilized enzyme support was used as a biosensor for determination of lactose in milk with excellent reproducibility and reusability. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: beta-Galactosidase; Bovine serum albumin; Glucose oxidase; Immobilization; Lactose assay

Protein-coated polymer as a matrix for enzyme immobilization: immobilization of trypsin on bovine serum albumin-coated allyl glycidyl ether-ethylene glycol dimethacrylate copolymer - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Kumaraguru, Thenkrishnan; Bajja, Sreedhar; Fadnavis, Nitin W.; Addepally, Uma; Rajdeo, Kishor; Ponrathnam, Surendra; Deokar, Sarika Babasaheb (Biotechnology Progress, 2014)
Allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) shows excellent bovine serum albumin (BSA) adsorption (up to 16% (w/w)) at pH 8.0 and the adsorbed BSA is strongly bound. This protein-coated polymer provides a novel matrix with naturally existing functional groups such as thiol, amino, and carboxylic acid that are available for covalent immobilization of functional enzymes. Employing appropriate strategies, trypsin as a model protein was covalently bound to BSA-coated matrix both independently, and in a stepwise manner on the same matrix, with less than 5% loss of enzyme activity during immobilization. Glutaraldehyde crosslinking after immobilization provide stable enzyme preparation with activity of 510 units/g recycled up to six times without loss of enzyme activity. AFM studies reveal that the polymer surface has protein peaks and valleys rather than a uniform monolayer distribution of the protein and the immobilized enzyme preparation can best be described as polymer supported cross-linked enzyme aggregates (CLEAs). (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:317-323, 2014
Keywords: allyl glycidyl ether; Bovine serum albumin; ethylene glycol dimethacrylate; Immobilization; Trypsin

Immobilization of pectinase on reusable polymer support for clarification of apple juice - Rajdeo, Kishor; Harini, Tirunagari; Lavanya, Kuna; Fadnavis, Nitin W. (Food and Bioproducts Processing, 2016)
Pectinase (E.C.3.2.1.15) was successfully immobilized on recyclable polymer matrix. The immobilization matrix was prepared by reaction of polyethyleneimine (mol. wt. 70,000) with epoxy-activated acrylate copolymer DILBEAD-VWR. The enzyme pectinase was first adsorbed on the polymer at pH 7.0 via ion exchange and then stabilized by crosslinking with dextran aldehyde. While the free enzyme shows a pH-optimum of 5.0, the immobilized enzyme exhibited high level of activity in a broad pH range of pH 3.0-7.0. Although the thermal stability of free and immobilized enzymes was similar, at room temperature, the immobilized enzyme could be recycled more than 10 times with loss of less than 5% of its activity during clarification of apple juice. On the eventual loss of enzyme activity, the immobilized enzyme and dextran aldehyde can be easily removed from the polymer by a simple treatment with 1N HCl and the polymer can be reused for immobilization of a fresh batch of enzyme. This support also can be reused several times, making the process economically attractive. The properties of apple juice treated with immobilized enzyme were similar to those of that treated with free pectinase. (C) 2016 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Apple juice; Dextran aldehyde; Immobilization; Pectinase; Polyethyleneimine; Polymer

Palladium supported ionic liquid phase catalyst (Pd@SILP-PS) for room temperature Suzuki-Miyaura cross-coupling reaction - More, S.; Jadhav, S; Salunkhe, R.; Kumbhar, A. (Molecular Catalysis, 2017)
A new Pd-SILP based on amino functionalized imidazolium ionic liquid immobilized on Merrifield resin (Pd@SILP-PS) has been synthesized. The catalyst was characterized by different techniques like FT-IR, SEM-EDS, TEM, TGA-DTA and XPS. The catalyst has shown to be highly active in Suzuki-Miyaura cross-coupling reaction of various aryl halides and aryl boronic acids in ethanol at room temperature. The activity of catalyst and the nature of product were highly dependent on the type of the solvent used, as well as the substituents present on the aryl halides. The protic polar solvent ethanol gave desired cross-coupling product in good to excellent yields at room temperature. However the aprotic polar solvent THF gave homocoupling product. The catalyst showed at least five times recyclability without a decrease in product yield.
Keywords: Immobilization; Ionic liquid; Palladium; SILP; Suzuki-Miyaura reaction

Synthesis, characterization and catalytic study of mesoporous carbon materials prepared via mesoporous silica using non-surfactant templating agents - Pagar, Nitin S.; Karandikar, Prashant R.; Chandwadkar, Asha J.; Deshpande, Raj M. (Journal of Porous Materials, 2020)
Mesostructured silica materials with surface area in the range of similar to 700-900 m(2)/g have been prepared using hydroxy-carboxylic acid compounds such as tartaric acid, malic acid and citric acid (low cost non-surfactant template/pore forming agents) and tetraethylorthosilicate (TEOS) as silica source by sol-gel reaction. The templates were removed by either soxhlet extraction or calcination method. Mesoporous carbon molecular sieves were then prepared by carbonizing sucrose inside the pores of the above prepared mesoporous silica using sulfuric acid as a catalyst. The materials were characterized by FTIR spectroscopy, powder X-ray diffraction (XRD), N-2-sorption studies, microanalysis, thermal analysis and transmission electron microscopy (TEM). The resulting carbon material shows relatively higher surface area (similar to 1100 m(2)/g), narrow pore size distribution and pore diameter of 4-5 nm. The mesoporosity of carbon material arises from interconnecting channels arrangements of mesoporous silica template. The mesoporous carbon material was used as a support for the immobilization of rhodium complex [HRhCO(TPPTS)(3)] by ossification method. The prepared catalyst has been tested for the hydroformylation of higher olefins. The activity of the catalyst was improved by 20-30% as compared to the catalyst prepared from a conventional activated carbon support.
Keywords: Carbonization; Hydroformylation; Immobilization; Low cost templates; mesoporous carbon; Mesoporous silica

Immobilization of HPW on UiO-66-NH2 MOF as efficient catalyst for synthesis of furfuryl ether and alkyl levulinate as biofuel - Mulik, Nagesh; Bokade, Vijay (Molecular Catalysis, 2022)
Phosphotungustic Acid (HPW) is an inorganic super acid, that is highly soluble in polar solvents limiting its applicability as acid catalysis. To overcome these limitations immobilization of HPW was carried out at room temperature by protonation of-NH2 group of UiO-66-NH2 MOF to UiO-66-NH2-HPW. ATR-FTIR spectroscopy and XPS results confirmed the protonation and chemical interaction between HPW and UiO-66-NH2. STEM-EDS mapping showed homogeneous distribution of HPW on UiO-66-NH2. BET and NH3-TPD confirmed the reduction in specific surface area, total pore volume, and increase in total acidity for UiO-66-NH2-HPW. Further, powder XRD, SEM, and HR-TEM prevailed that there is no change in phase and morphology after post-synthetic modification of UiO-66-NH2. The prepared catalyst is found to be effective for etherification and alcoholysis of furfuryl alcohol (FALc) to Furfuryl ether (FE) and Alkyl levulinate (AL). UiO-66-NH2-HPW has shown 97 mol % FALc conversions in ethanolic media and 31 mol% Ethyl furfuryl ether (EFE) yield and 29 mol% Ethyl lev-ulinate (EL) yield. UiO-66-NH2-HPW is also found to be efficient for the multistep conversion of Furfural (FFR) to FALc, FE, and AL.
Keywords: Alcoholysis; etherification; Immobilization; Phosphotungstic acid; UiO-66-NH2-HPW